Kisah Ratu Balqis dalam Tafsir Nusantara dan Relevansinya pada Konteks Partisipasi Politik di Indonesia (Studi Komparatif: Penafsiran Hasbi Ash-Shidieqy, HAMKA, serta Quraish Shihab) - Reza Firmansyah; Asep Ahmad Fathurrohman; Eni Zulaiha (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2026)
Reexamining the representation of women in the Qur'an is essential for understanding contemporary gender discourse, particularly amid the persistence of patriarchal perceptions that continue to influence women's political participation in Indonesia. This study aims to analyze the interpretation of Queen Balqis in Indonesian Qur'anic exegesis (Tafsir Nusantara) and examine its relevance to women's political participation in contemporary Indonesia. Employing a qualitative library research design, this study adopts a comparative exegesis approach integrated with feminist hermeneutics and socio-political contextualization. The primary sources consist of Tafsir An-Nūr by Hasbi Ash-Shiddieqy, Tafsir Al-Azhar by Hamka, and Tafsir Al-Miṣbāḥ by Quraish Shihab, supported by relevant academic literature. The findings reveal that all three exegetes recognize Queen Balqis as a legitimate political leader whose leadership is characterized by rationality, consultation (shūrā), diplomacy, and public welfare. Their differences primarily lie in methodological orientation: Hasbi emphasizes normative-juridical principles, Hamka highlights moral and ethical dimensions, while Quraish Shihab adopts a contextual and maqāṣid al-sharī'ah approach. Collectively, these interpretations demonstrate that the Qur'an does not reject women's political leadership on the basis of gender but evaluates leadership according to competence, justice, and public benefit. Consequently, Tafsir Nusantara offers an inclusive and contextually relevant Qur'anic framework for strengthening women's political participation in contemporary Indonesia.